The Representation of Positive Affirmations of Parents in the Film Inside Out (2015): A Study of Roland Barthes' Semiotic Analysis - Shafa Raihan Imadia; Ayu Larasati (CV Edujavare Publishing, 2026)
This study examines the representation of positive parental affirmation in the film Inside Out (2015). It aims to analyze how positive parental affirmation is represented through verbal and nonverbal signs and to identify its denotative, connotative, and mythical meanings using Roland Barthes' semiotic analysis. This study employed a descriptive qualitative method with Roland Barthes' semiotic approach. The unit of analysis consisted of seven scenes depicting interactions between Riley and her parents containing positive affirmation. The data were analyzed through three levels of meaning: denotation, connotation, and myth, and were interpreted using Positive Communication Theory, which includes acceptance, validation, empathy, and encouragement. The findings indicate that parental affirmation is represented through verbal and nonverbal communication in the forms of acceptance, emotional validation, empathy, encouragement, parental support, and attentive presence. At the level of myth, the film constructs the idea of an ideal family that accepts, understands, and supports children through positive communication. This study concludes that Inside Out (2015) represents positive parental affirmation as a meaningful form of family communication reflecting social values.